Exit as Care: How Motherhood Mediates Women’s Exodus From Violence in Mexico and Central America - López Ricoy, Ana (Violence against women, 2022)
Today, growing numbers of mothers and children are fleeing Mexico and Central America. Most scholars attribute this displacement to organized crime, and a few note the importance of gender violence in driving women’s migration. Yet, less has been said about how violence affects motherhood or how motherhood shapes women’s decisions to leave. Drawing on 44 in-depth interviews with Mexican and Central American women seeking U.S. asylum, we show how multifaceted violence intensifies the burdens on mothers. At the same time, we argue, motherhood can offer a source of agency in contexts of normalized violence, inspiring women to flee.